A Juridical Review of The Sultanate Lands and Villager Land Under The Governor Regulation Number 32 of 2007 on The Use of Villager Land After The Enactment of Act No. 6 of 2014 on Village - Damar Dwi Kuncoro; Suroto Suroto; Amin Purnawan (Jurnal Akta, 2018)
The background of this research was the issuance of Act No. 6 Of 2014 about the Village. In one of its provisions contains the wealth of the village in the form of land certified on behalf of the Village Government. While the status of Villager Land in the Special Region of Yogyakarta is the land of the Sultanate. The research aimed to get an explanation of the status of Villager Land and to know the legal consequences that will arise with respect to the utilization of the Sultanate land associated with the Villager Land after the enactment of Act No. 6 of 2014, when associated with the Provincial Governor Regulation No. 34 of 2017 on Utilization of Villager Land. This research used sociological juridical approach (primary data) and direct interviews to the community in Sleman Yogyakarta (secondary data) and literature study. The result of the research shows that with the enactment of the Yogyakarta Governor Regulation, the Villager Land that comes from the right of anggaduh (Javanese Lng.) and the substitute land has been certified on behalf of the Village Government for the transfer of rights to the property of the Sultanate. Determination of the Sultanate as a Legal Entity which can become the subject of land ownership resulted in a change of status of the Sultanate institution to be equivalent to the private Legal Entity. The consequences of such changes resulted in changes in the management of the Sultanate land and the burden of obligations and responsibilities that must be met by the Sultanate for the management of the Sultanate land.Keywords: Juridical Review; Sultanate land; Villager Land